IMPLEMENTASI METODE TOTAL PRODUCTIVE MAINTENANCE (TPM) DALAM MENENTUKAN EFEKTIFITAS STASIUN PENGGILINGAN TEBU - Ghaffar, Jakfat Maulid; Arbiantara, Hari; Mulyadi, Santoso; Sanata, Andi; Djumhariyanto, Dwi (Jurusan Teknik Mesin, 2024)
The milling station is a station where sugar cane-based sugar is produced, readiness is needed especially from the point of view of equipment maintenance in order to support the production process. Total Productive Maintenance (TPM) is one method of maintenance approach with Overall Equipment Effectiveness (OEE) is one of the measuring tools in calculating the effectiveness of equipment. Failure Mode and Effect Analysis (FMEA) is one method in analyzing the cause and effect of each device so that later it is hoped that this research can determine the value of the effectiveness of the equipment and provide recommendations for improvements. The calculation of the effectiveness of the equipment at the milling station that the effectiveness values ​​from 2013 to 2017 are 75.87%, 84.17%, 87.58%, 61.53% and 92.59%. In 2013, 2014 and 2016 showed that the value of effectiveness is still below the standards of world class effectiveness values. Factors that influence the effectiveness of 2013 to 2017 are Reduce Speed ​​Losses and Set-up adjustments time. Improvement of recommendations according to the TPM pillar in increasing productivity is 5S (Seiri, Seiso, Seiton, Seiketsu, and Setsuke). Keyword: Total Productive Maintenance (TPM), Overall Equipment Effectiveness (OEE), Failure Mode and Effect Analysis (FMEA).